Caring for oneself to care for others: physicians and their self-care - Sanchez-Reilly, Sandra (2013)
It is well known that clinicians experience distress and grief in response to their patients' suffering. Oncologists and palliative care specialists are no exception since they commonly experience patient loss and are often affected by unprocessed grief. These emotions can compromise clinicians' personal well-being, since unexamined emotions may lead to burnout, moral distress, compassion fatigue, and poor clinical decisions which adversely affect patient care. One approach to mitigate this harm is self-care, defined as a cadre of activities performed independently by an individual to promote and maintain personal well-being throughout life. This article emphasizes the importance of having a self-care and self-awareness plan when caring for patients with life-limiting cancer and discusses validated methods to increase self-care, enhance self-awareness and improve patient care.